Gridlock versus harmony: the effect of presidential cycle. (1st January 2013) - Sy, Oumar; Zaman, Ashraf Al
In this paper, we investigate the impact of the interactions between presidential cycle and political environment on stock returns. We find that neither presidential cycle nor political environment has a significant impact on big firms. In contrast, we find that small firms perform significantly better under Democratic presidencies (relative to Republican presidencies) during harmonies, when one party simultaneously controls the executive and legislative bodies. Our results suggest that the recent evidence by Beyer et al. (2006) that a harmonious political environment is better for small firm investors is true only when the Democrats are in power.